DAYA TAMPUNG SUNGAI TAKUANA TERHADAP BEBAN PENCEMAR SEKITAR TAMAN HUTAN RAKYAT SULTAN SYARIF HASIM - Marganda Simamora; Rifardi Rifardi; Manyuk Fauzi (Jurnal Ilmu Lingkungan, 2018)
This study aims to analyze the relationship of land use change or changes in land cover with the water quality of the River Takuana and the relationship of pollutant load with the capacity of the Takuana River. River carrying capacity is obtained by the Mass Balance method on the parameters of BOD, COD, DO, TSS, NH3-N, pH and Temperature. Sampling was carried out at three points based on the division of the river. The results showed that there was a relationship between land conversion to river water quality as evidenced by the statistical calculation of the t-hit value indicating that the significance of TSS was 1.7 <0.05, the significance was 0.017 <0.05, which means that TDS and TSS had no significant effect on land conversion while BOD, DO, COD, pH. temperature and NH3N have a relationship with the extent of the function, because the significance of the results is smaller or equal to 0.05 BOD the significance is 0.013 <0.05, DO significance is 0.030 <0.05, the significance temperature is 0.017 <0.05 and NH3N 0.052 <0.05. River carrying capacity is influenced by the amount of pollutants and river water rate while river pollutant load is influenced by the amount of pollutants and water discharge. So the higher the rate of water also affects the river water discharge, based on the calculation of pollutant load and carrying capacity shows that there is a relationship that the amount of pollutant load for the overall parameters of pollutants exceeds the capacity of polluting the Takuana River. for TSS parameters the amount of pollutant load is 57,600 mg / sec and TSS capacity is 37.69 mg / liter, but still meets the class II quality criteria based on Government Regulation No. 82 of 2001 of 50 Mg / liter. TDS pollutant load is 30,430 mg / second, TDS capacity is 21.52 mg / liter but pollutant load still meets class II quality criteria, DO pollutant load is high but still meets class II quality criteria. For high pollutant loads COD, BOD and NH3-N result in lower capacity and have exceeded the class II quality criteria according to GovernmentRegulation No. 82 of 2001. The higher the pollutant load that enters the river, resulting in lower river capacity